2016
DOI: 10.1515/ama-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Direct Current and Pulsed Direct Current Plasma Nitriding of Ferrous Materials a Critical Review

Abstract: Nowadays, the improvement of ferrous materials performance is a problem of high interest. One of well-known wear-and corrosion properties improving technique is plasma nitriding, in which elemental nitrogen is introduced to the surface of a metal part for subsequent diffusion into the material. As a result, a compound, "white" layer and a diffusion zone are formed at the detail's surface. Most of the authors positively describe the effects of surface ion nitiding. On the other hand, there are also reports on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
(69 reference statements)
0
5
0
1
Order By: Relevance
“…In case of thermo-chemical treatments, e.g. nitriding or carburizing, a common method of determining the thickness of a modified layer is to measure the thickness of the hardened layer of the specimen -the case depth [8]. To investigate the effective layer thickness, a series of hardness measurements in a perpendicular direction to the coating is made on the cross section of the sample (Figure 3).…”
Section: Thickness Measurementsmentioning
confidence: 99%
“…In case of thermo-chemical treatments, e.g. nitriding or carburizing, a common method of determining the thickness of a modified layer is to measure the thickness of the hardened layer of the specimen -the case depth [8]. To investigate the effective layer thickness, a series of hardness measurements in a perpendicular direction to the coating is made on the cross section of the sample (Figure 3).…”
Section: Thickness Measurementsmentioning
confidence: 99%
“…The routinely applied surface modification methods include but are not limited to physical vapor deposition, chemical vapor deposition, thermochemical treatment, etc. [19][20][21][22]. Among applied coatings, titanium nitride (TiN) and diamond-like-carbon (DLC) are routinely used to improve tribological performance of metallic materials.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the wear and corrosion performance of implant alloys, numerous coatings, e.g., titanium nitride (TiN) and diamond-like-carbon (DLC) [10], as well as the thermochemical treatments [11], are used. Nevertheless, it has been shown that in the long-term in vivo usage, the protective films can be worn out of the implant surface [12].…”
Section: Introductionmentioning
confidence: 99%